Educational sevices quality assessment methods classification - N. S. Bugro; V. N. Yarmolik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Comprehensive analyses of different scaling technique to be used for high education service quality estimation are provided. The most well-known scaling techniques have been described with simple illustrating example. The Likert scaling approach has been pointed out as the more suitable approach for high education service quality estimation.